FORENSIC ANALYSIS OF WIRELESS NETWORKS - Anggraini, Dyah; Syahbuddin, Syahbuddin (Majalah Ilmiah Matematika Komputer, 2006)
Wireless communications has been accepted by many organizations and users asit allows to be flexible and portable with increased productivity and lowerinstallation costs. It can be moulded and designed to address different usage anduser needs. WLAN able devices allow users to move their wireless devices fromplace to place within the office without the need of wires and without losing networkconnectivity. It is a well known fact that the wireless networks are vulnerable tomany attacks. Some of the attacks may include interception of sensitive informationthat is not encrypted and transmitted between two wireless devices. Ad hoctransmissions within the network can even compromise the security of a network.Intruders can interfere from inside or out of the network in order to gain connectivityto network management controls and thereby disrupting network resources. Inmost cases the attackers cannot be traced or the purpose of the attack is notknown. Even though we have access to the AP's log files, it has very lessinformation stored in it. Most of the AP's do not provide syslog facilities so that thelogs can be stored at some other server. With the increase in the number of attacktools, security of wireless technologies has become a primary concern. This paperis all about building a device that would be able to watch all the WLAN data andanalysing all the traffic coming and going out of the wireless AP.Keywords: Wireless local area network (WLAN), Access Point (AP), Forensic, WiFiTools,WEP, WPA, 802.11INTRODUCTION